A STUDY OF FACTORS INFLUENCING EVS IN SIMULTANEOUS INTERPRETING - JIANG, WEN (Chinese Language and Culture Journal, 2020)
EVS is an important concept of simultaneous interpreting. The interpreter should adjust and adapt the pace of a speech in order to improve the fluency and accuracy of interpretation under different conditions. The study will describe different aspects of affecting EVS in a simultaneous interpreting so as to provide the strategies of improving the accuracy and fluency of interpretation.